Strategies for overcoming the problems of intercultural communication in Chinese students' EFL teaching - Lin, Liyuan (Вестник Томского государственного университета)
This study investigates effective strategies to enhance intercultural communicative competence (ICC) among Chinese EFL learners through a mixed-methods approach. Drawing on Wen Qiufang's intercultural framework and China's 2020 EFL guidelines, we analyzed survey data from 255 undergraduates/graduates(128 males, 127 females) via SPSS(Statistical Package for the Social Sciences, as one of the most influential statistical analysis software globally, it integrates data management, statistical modeling, and visualization into a full-process analytical platform) 27.0.Findings reveal that technology-integrated comparative cultural analysis significantly improves ICC(M = 3.65, SD = 1.298),while highlighting persistent challenges in balancing Western and Chinese cultural content. The proposed Third Space Teaching Approach demonstrates efficacy in fostering hybrid cultural literacy through cognitive, affective, and behavioral strategies.